Speech Enhancement Using Hybrid Optimization Technique. (2016) - Anoop, V.; Rao, P.V.
Abstract: In this paper, an efficient method for speech enhancement based on hybrid optimization technique is proposed. Here the global evolutionary algorithms such as Cuckoo Search (CS) and Particle Swarm Optimization (PSO) are used to develop the hybrid optimization technique. The paper compares the efficiency of this hybrid technique with the conventional adaptive algorithms and CS algorithm. The parameter Signal to Noise Ratio (SNR) is used to evaluate the performance of these algorithms. The obtained result proves the efficiency of the proposed technique over conventional methods. The proposed hybrid method gives 28% better SNR.